On 1-sequentially additive graphs - Seoud M.A.; Jaber, Huda (Utilitas Mathematica, 2022)
In this paper, we determine all 1-sequentially additive graphs of order 6 by using an algorithm written in C++ programming language. We label some 1- sequentially additive families. Some labelings are based on Skolem and hooked Skolem sequences.